2015
DOI: 10.1111/jan.12767
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' views on patient self‐management: a qualitative study

Abstract: Nurses had distinct perceptions about self-management and their own role in self-management support. Social and emotional tasks of living with a chronic condition were, however, overlooked. Nurses seem to lack sufficient training and practical interventions to provide self-management support that meets the integral needs of patients with a chronic condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 41 publications
(52 reference statements)
5
69
0
Order By: Relevance
“…Initially, they associated empathy negatively with endless listening and pretending to be interested, and their initial interaction and dialogues with the older adults were found to be scarce. Their unfamiliarity resulted in feelings of helplessness, which might have contributed to the steering behaviours noted in this study, as well as in several other studies,28 29 and demonstrated the need for introducing generic autonomy supportive conversational skills among nurses.…”
Section: Discussionsupporting
confidence: 63%
“…Initially, they associated empathy negatively with endless listening and pretending to be interested, and their initial interaction and dialogues with the older adults were found to be scarce. Their unfamiliarity resulted in feelings of helplessness, which might have contributed to the steering behaviours noted in this study, as well as in several other studies,28 29 and demonstrated the need for introducing generic autonomy supportive conversational skills among nurses.…”
Section: Discussionsupporting
confidence: 63%
“…Adequate self‐management support implies that nurses share an understanding of their role and tasks in self‐management (Been‐Dahmen, Dwarswaard, Hazes, van Staa, & Ista, ). However, nurses vary in their understanding of what self‐management entails and predominantly perceive self‐management as incorporating the traditional biomedical approach, which is premised on compliance with professional advice, the monitoring of symptoms, and patients’ individual responsibility to self‐manage their chronic condition (Sadler, Wolfe, & McKevitt, ).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of both statistical and practical respects, the key findings were that individuals with lower education levels had significantly poorer knowledge of their health condition and treatment; those with a mental health problem were worse at coping with the effect of their condition on their physical and emotional well‐being and smokers did not have as strong a partnership in treatment or ability to recognize and manage their symptoms as compared to non‐smokers. These key findings could facilitate nurse practitioners (Been‐Dahmen et al, ; van Hooft et al, ) and health systems to develop interventions that are better directed to individual needs.…”
Section: Discussionmentioning
confidence: 99%